Green electrospinning - Horzum,N.; Demir, Mustafa Muammer; Muñoz-Espí,R.; Hood,M.A.; Demir,M.M.; Crespy,D. (De Gruyter, 2019)
In the last two decades, electrospinning has grown in popularity; however, the majority of the setups are based on solution processing from toxic organic solvents. As green processing and environmental stewardship have also become important in recent years, for political and economic reasons, the subsequent increase in demand for the scaling up of electrospinning requires that an environmentally toxin-free process be championed. This book comprehensively addresses clean and safe electrospinning for the fabrication of green nanofibers and evaluates their potential applications. © 2019 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.
Keywords: Clean electrospinning; Environmentally friendly electrospinning; Green fibers; Safe electrospinning; Solvents